Locomotion control of a biomimetic robotic fish based on closed loop sensory feedback CPG model - Korkmaz, Deniz; Koca, Gonca Ozmen; Li, Guoyuan; Bal, Cafer; Ay, Mustafa; Akpolat, Zuhtu Hakan (Taylor & Francis Ltd, 2021)
This paper presents mechatronic design and hierarchical locomotion control of a biomimetic robotic fish for three-dimensional swimming modes. Inspired by biological features of Lamprey, a closed loop sensory feedback Central Pattern Generator (CPG) model is adapted to hierarchical control mechanism in order to provide robust and effective biomimetic control structure. A sensory feedback mechanism plays an important role to react external stimuli from environment. In addition, a closed loop fuzzy logic control structure is developed as a brain model to decide adaptive swimming modes according to sensory information. In order to provide three-dimensional motion abilities, the Centre of Gravity (CoG) control mechanism is designed and controlled by a back-forth proportional control structure. Experimental results are obtained to prove the CPG-based closed loop sensory feedback control structure with the developed robotic fish prototype.
Keywords: Mechatronic Design; Gait